From Neutral to Ionic Species: Syntheses and X‐ray Crystallographic and Multinuclear NMR Spectroscopic Studies of Li···P(SiMe3)–PtBu2 and Its Solvent Complexes. Issue 1 (19th November 2013) - Sattler, Ewald; Matern, Eberhard; Rothenberger, Alexander; Okrut, Alexander; Bombicz, Petra; Fernández, Ignacio; Kovács, Ilona
Abstract: Li(THF)3 P(SiMe3 )–P t Bu2 (1, THF = tetrahydrofuran) has been prepared by the reaction of (Me3 Si)2 P–P t Bu2 with n ‐butyllithium in THF and isolated in good yields. Compound1 eliminates THF in vacuo to yield the dimeric [Li(THF)P(SiMe3 )–P t Bu2 ]2 (2 ). By metalation of H(SiMe3 )P–P t Bu2 with n ‐butyllithium in hexane, the solvent‐free derivative [Li(Me3 Si)P–P t Bu2 ]4 (3 ) has been prepared. Compounds1 –3 form the ionic species [Li(TMEDA)2 ] + [(Me3 Si)P–P t Bu2 ] – [4, TMEDA = Me2 N(CH2 )2 NMe2 ] and [Li(12‐crown‐4)2 ] + [(SiMe3 )P–P t Bu2 ] – (5 ) with TMEDA and 12‐crown‐4, respectively, in solution. The molecular structures of1 –5 were established by single‐crystal X‐ray diffraction. Compound3 forms a cyclic tetramer with a flat butterfly geometry. Extensive solution NMR spectroscopic investigations have shown that all species except for3 exist in the same form in solution as in the solid state. Moreover, multinuclear variable‐temperature NMR studies showed that2 is involved in a rapid conversion between conformers at 298 K, which can be slowed down on the NMR timescale at 183 K. Abstract : Single‐crystal X‐ray structural determinations of Li(L) n (Me3 Si)P–P t Bu2 [L = tetrahydrofuran, n = 3, 1, 0; L = Me2 N(CH2 )2 NMe2, n = 2; L = 12‐crown‐4, n = 2] show that the higher the coordination number of Li, the longer the Li–P distance is. Multinuclear NMR studies have proven that all compounds except the donor‐free tetramer have the same molecular structure in solution as in the solid state.